Smart door lock based on bluetooth and IoT - Hashim Al-Tuma, Khalid Asaad (2019)
Numerous control systems for home security purposes have been designed over the years to prevent access to the unauthorized user. The main aim of the control systems is for providing a security for our lives and property for home, schools, offices etc. Therefore, it is important to have a smart technology of achieving this goal. Automatic door system has become a standard feature on many different types of buildings and homes. Further, they are becoming popular due to an effective electronic device which provides high security. Home security has been a major issue because of the increase in crime rate and everybody wants to take proper action to prevent unauthorized users. There was a necessity to automate home so that user can take advantage of the IoT technology as well. Therefore, this project is to develop a prototype of a door security code system using smart device Bluetooth as a key and interface with the IoT in order to monitoring the system. This project was successful working and thus, this design can be a good candidate for home security applications.